Pengelolaan limbah elektronika di DKI Jakarta menggunakan pendekatan Soft System Methodology - Dino Rimantho (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2020)
In the last few decades, the growth of electrical and electronic products has significantly increased, marked by an increase in demand and sales of its products globally. It affects the product's service life to be shorter, which ends up becoming waste faster. Some factors causing the complexity of electronic waste management problems are the roles and functions of stakeholders (government, informal sector, manufacturing industry and sanitation office). This article analyzed the electronic waste management problems and alternative solution through the waste management model using the Soft System Methodology (SSM) approach. Data and information were obtained through literature studies and in-depth discussions with several experts. The study results show that applying the SSM method produces a conceptual model illustrating the activities between sub-elements to improve electronic waste management. The SSM model was built to improve waste management and reduce its negative impacts. The role relevance and synergy of actors such as the central government, local governments, and business actors (waste businesses, including scavengers) determine the objectives' success. As a major stakeholder, Ministry of Environment and Forestry plays a role in designing policies and programs, supported by Ministry of Industry, DKI Jakarta Sanitation Service and other related agencies.